The Relationship Between Empathy and Stress in the Context of Helping Professions - Radulović, Aleksandra Z.; Lalatović, Staša V.; Mirjanić, Tijana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Empathy represents an important and complex psychological phenomenon, comprising both affective and cognitive components, and it is fundamental to high-quality care in helping professions. This research aimed to explore the associations between stress (occupational stress and stressful life events) and empathy (both its affective and cognitive components) across various groups of helping professionals (doctors, special educators and rehabilitators, and psychologists), compared to individuals employed in non-helping professions (i.e., engineers). A total of 243 participants completed self-reported online questionnaires. Significant differences in empathy scores were found between helping and non-helping professionals on the cognitive empathy scale, with helping professionals scoring higher. Participants did not differ significantly in terms of occupational stress levels or the number of stressful life events, but respondents from helping professions rated their life events as more severe than those in non-helping professions. Our hypothesis—that experiences of stress could predict empathy levels in helping professionals—was confirmed with respect to affective and global empathy. The severity of stressful life events emerged as the most relevant stress-related variable in predicting empathy, especially its affective component. The implications of these findings, as well as recommendations for future research, are discussed.